Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia - Uiblein, Franz; Gledhill, Daniel C.; Peristiwady, Teguh (Zootaxa, 2017)
Two new goatfishes of the genus Upeneus (Mullidae) belonging to the putative japonicus species group are described and compared with congeneric species using a large set of meristic, morphometric and colour characters. Upeneus farnis n. sp. Uiblein & Peristiwady is described based on 14 adult specimens (> 65 mm SL) collected at the local fish market of Bitung, NE Sulawesi, Indonesia. Upeneus spottocaudalis n. sp. Uiblein & Gledhill is described based on 16 adult and seven subadult specimens (< 65 mm SL) specimens collected by trawling surveys off NE Australia and one non-type adult specimen collected off southern Indonesia. The new species differ from all other congenerics in the combination of dorsal-fin spine, pectoral-fin ray and gill raker numbers, body and head depth, length of head, snout, barbels and paired fins, height of anal and dorsal fins, eye size, and body, barbel and caudal-fin colour patterns. When compared in detail with the 12 other species of the japonicus group, Upeneus farnis n. sp. can be distinguished by smaller eyes, shallower anal and second dorsal fins, more pectoral-fin rays and gill rakers, and the lower caudal-fin lobe almost completely dark pigmented. Upeneus spottocaudalis n. sp. differs from the other japonicus-group species in larger eyes, higher second dorsal fin, pectoral fin shorter than pelvic fin, and presence of rounded, dark spots on the lower caudal-fin lobe. Subadults differ from adult U. spottocaudalis n. sp. mainly in longer pelvic fins. The high diversity of Upeneus species in relation to divergence in colour patterns and the need of further taxonomic exploration of the genus Upeneus is discussed.